Pengaruh Konsumsi Susu Kedelai terhadap Blood Clotting Time - Kurniati, Ika Dyah; Astuti, Yoni (Universitas Muhammadiyah Yogyakarta, 2008)
Soy is raw material of food know and tempeh which have so common among Indonesian society. In the reality soy not only made as food. Soy also can be made milk. High enough protein that content at soy milk have important role in calcium metabolism. Calcium besides good for forming of bone and tooth, and also maintain health of nerve function and muscle, also to help blood coagulation at hurt. The objective of this esearch is to measure the duration time of blood coagulation (clotting time) at subject which given soy milk and subject which do not given soy milk, and also compare the result of measurement between both. Research design used is pretest - post test control group design, using subject 10 people and divided randomly in 2 groups. Group I is group of subject which given soy milk 200 cc twice one day during 14 day. Group II is negative control group and subject did not get treatment. Blood sample was taken before and after research, and measured it clotting time using modification way of Lee White ’s. Result of this research showed that consuming soy milk can quicken clotting time, but this influence were not significantly different (p 0,05). The average of clotting time of group I before given of soy milk 06.26 minut /ml and after it 05.07 minute/ml, average of clotting time of group II before research 04.38 minute/ml and after research 06.36 minut/ml.Kedelai adalah bahan baku makanan pada tahu dan tempe yang sudah begitu melekat di kalangan masyarakat Indonesia. Kedelai juga dapat dijadikan susu. Kandungan protein yang cukup tinggi pada susu kedelai mempunyai peran penting dalam metabolisme kalsium. Kalsium selain berguna untuk pembentukan gigi dan tulang, serta mempertahankan kesehatan fungsi syaraf dan otot, juga membantu pembekuan darah pada luka.Tujuan penelitian ini adalah untuk mengukur lamanya waktu pembekuan darah (bloodclotting time) pada subjek yang diberi susu kedelai dan subjek yang tidak diberi susu kedelai, serta membandingkan hasil pengukuran antara keduanya. Rancangan penelitian yang digunakan adalah pretest - post test control group design, dengan menggunakan subjek sebanyak 10 orang dan dibagi secara acak dalam 2 kelompok. Kelompok I adalah kelompok subjek yang diberikan susu kedelai 200 cc dua kali sehari selama 14 hari. Kelompok II merupakan kelompok kontrol negatif dan subjek tidak mendapat perlakuan. Sample darah diambil pada sebelum dan sesudah penelitian, dan diukur clotting time-nya dengan menggunakan modifikasi dari cara Lee White. Hasil penelitian menunjukkan bahwa susu kedelai dapat mempercepat blood clotting time, namun tidak signifikan (p 0,05) secara statistik. Rerata clotting time kelompok I sebelum pemberian susu kedelai 06.26 menit/ml dan setelah pemberian 05.07 menit/ml. Rerata clotting time kelompok II sebelum penelitian 04.38 menit/ml dan setelah penelitian 06.36 menit/ml.